2022
DOI: 10.1093/ehjci/jeac082
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between ischaemia, coronary artery calcium scores, and major adverse cardiovascular events

Abstract: Aims Positron emission tomography (PET) myocardial perfusion imaging (MPI) is often combined with coronary artery calcium (CAC) scanning, allowing for a combined anatomic and functional assessment. We evaluated the independent prognostic value of quantitative assessment of myocardial perfusion and CAC scores in patients undergoing PET. Methods and results Consecutive patients who underwent Rb-82 PET with CAC scoring between 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…However, the data was obtained from routine standardized forms with only a small proportion of missing values, and almost all variables were objective. Second, our institution had a higher rate of revascularization, accounting for 73% of all MACE, compared to other centers where it ranged from 6-42% [35][36][37]. This indicates that a high CAC score may have served as a guide for a signi cant number of revascularizations in our study, potentially in ating the incidence of MACE.…”
Section: Discussionmentioning
confidence: 74%
“…However, the data was obtained from routine standardized forms with only a small proportion of missing values, and almost all variables were objective. Second, our institution had a higher rate of revascularization, accounting for 73% of all MACE, compared to other centers where it ranged from 6-42% [35][36][37]. This indicates that a high CAC score may have served as a guide for a signi cant number of revascularizations in our study, potentially in ating the incidence of MACE.…”
Section: Discussionmentioning
confidence: 74%
“…We did not have adequate statistical strength to perform stratified CACS analyses; however, recent studies have reported higher annualized rates of cardiac events in patients with impaired MFR across all groups of CACS (0, 1-99, 100-399, and >399), highlighting the independent predictive value of MFR. 27,28 We report MFR to hold prognostic value for noncardiac death independently of reversible perfusion defects. One possible explanation for the association could be linked to systemic inflammation, as seen in patients with CMD 29 and rheumatoid arthritis.…”
Section: Mfr: a Predictor Of Mortalitymentioning
confidence: 87%
“…We did not have adequate statistical strength to perform stratified CACS analyses; however, recent studies have reported higher annualized rates of cardiac events in patients with impaired MFR across all groups of CACS (0, 1–99, 100–399, and >399), highlighting the independent predictive value of MFR. 27,28…”
Section: Discussionmentioning
confidence: 99%
“… 13 So, CAC has been shown not only as a good surrogate marker for the development of atherosclerosis but also as a good biomarker for risk stratification of cardiovascular disease (CVD) events among the general population (non-FH patients). 14 However, data on the effects of CAC on the FH phenotype are limited. 15 , 16 We aimed to determine if CAC is associated with CVD events, defined as CVD-related death, unstable angina, myocardial infarction, or staged revascularization among patients with heterozygous FH (HeFH) under primary prevention settings.…”
Section: Introductionmentioning
confidence: 99%